PENERAPAN PENDEKATAN KONTEKSTUAL DALAM SETTING PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIID SMP NEGERI 40 PEKANBARU - Fitriani Simatupang; Atma Murni; Suhermi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This classroom action research is aimed at improve learning process and mathamatics learning outcomes by implementing Contextual Approach in Setting Cooperative Learning with Numbered Heads Together (NHT) Type. The research subjects are 36 heterogenous academic ability level students of the VIID class of Junior High School 40 Pekanbaru in academic year of 2015/2016. The research implemented in two cycles in which each cycle consisted of four phases, i.e; namely planning, implementing, observing, and reflecting. By the end of a cycle, formative test was held. The data was collected by doing observation in teachers and students activities and formative test. The research shows if there is learning process improvement after the implementation Contextual Approach in Setting Cooperative Learning with Numbered Heads Together (NHT) Type. Most of the students participated actively and responsible in the learning process e.g. discussing, presenting student’s worksheet, responding to classmate’s presentation, and drawing the lesson conclusion. Additionally, the students afforded to answer the written test given by teacher well. Furthermore, the number of students passing passing Minimun Completeness Criteria (MCC) on base score, formative test I (first cycle), formative test II (second cycle) were respectively 33,3%, 44,4%, and 66,7%. The percentage of MCC achievement also indicates the increase after the implementation, thus it can be said that the students’ learning outcomes also increase. Finally, the research also shows that Contextual Approach in Setting Cooperative Learning with Numbered Heads Together (NHT) Type can improve mathematics learning process and learning outcomes of VIID class of Junior High School 40 Pekanbaru.